Suplementasi ekstrak albumin ikan gabus terhadap status gizi dan imunitas pasien stroke - Vivien Novarina Kasim; Sri Manovita Pateda; Veni Hadju; Nurhaedar Jafar (Jurnal Gizi Klinik Indonesia, 2017)
Background: Malnutrition and immunology change in stroke would affect the outcome of the stroke patient. The supplement of the extract of snakehead fish as an alternative is expected could reduce the effect pasca stroke.Objective: This study aims to assess the effect of snakehead fish supplementation on nutritional status, levels of albumin, TLC and TNF-α in stroke patients.Method: This type of study is a quasi-experimental, pre-test post-test group design, by providing treatment to the subject of research and treatment effects were measured and analyzed. Subjects were divided into two groups; a first group which receives 3 x 2 capsule of snakehead fish supplementation as well as diet and nutrition education (intervention group) and the second group that received only diet and education (control group).Results: From the results, it was found that nutritional status, which was obtained by measuring UAC in cases and controls are good (SG ≥ 85%) but no significant differences between them (p=0.914). There are significant differences between albumin levels before and after intervention (p=0.023) with an average increase of 0.2 g/dl, but not in the control group (p=0.931). For TLC values increased in the intervention group (990,5 sel/mm3) and a decrease in the control group (645,03 sel/mm3) with a significant difference in both groups (p=0.034). There was a decrease of TNFα in both group; for cases (mean=-2.91) and controls (mean=-2.58) with significant differences between the two groups (p=0.001).Conclusion: The supplementation of an extract of snakehead fish could increase the albumin and TLC level and decrease the TNFα in stroke patients.